The research of economic nature of goodwill - Савчук, Т. В. (Scientific Bulletin of Ivano-Frankivsk National Technical University of Oil and Gas (Series: Economics and Management in the Oil and Gas Industry), 2014)
Different approaches to the economic nature of goodwill are considered. The basic requirements for the recognition of an intangible asset as a separate accounting object have been analyzed. The conditions under which goodwill is an asset for the company are specified. Reasons due to which goodwill cannot be recognized as an intangible asset are justified and specified. The causes of goodwill are investigated. (the reasons of goodwill appearance are investigated). Different approaches to its assessment in recognizing are pointed (mentioned). Existing approaches to classification of goodwill are systematized and generalized. The influence of the classification of goodwill on its subsequent accounting is determined.